Market Selection, Reallocation, and Restructuring in the U.S. Retail Trade Sector in the 1990s - Foster, Lucia; Haltiwanger, John; Krizan, C. J (The Review of Economics and Statistics, 2006)
The U.S. retail trade sector underwent a massive restructuring and reallocation of activity in the 1990s with accompanying technological advances. Using a data set of establishments in that sector, we quantify and explore the relationship between this restructuring and reallocation and labor productivity dynamics. We find that virtually all of the labor productivity growth in the retail trade sector is accounted for by more productive entering establishments displacing much less productive exiting establishments. The productivity gap between low-productivity exiting single-unit establishments and entering high-productivity establishments from large, national chains plays a disproportionate role in these dynamics. Copyright by the President and Fellows of Harvard College and the Massachusetts Institute of Technology.